The changes of the firstformers‘ physical qualities - Muratchodžajeva , G. (Psichologija, 1972)
The article deals with the experimental research in the changes of physical capacity for work of first formers in a week’s cycle during the whole year. The results of the research can be used for working out scientific recommendations for stirring up physical and mental activities of the pupils. The article describes the researches carried out with the help of the electrochastotometre and electrotensodinamograph, as well as physical training of the pupils. The article also states the changes in the frequency of the movement, the strength of the hand, the endurance of 50% of the maximum strength and the indivisible index of the muscle’s activity in kg/second. All these experimental results are interesting from the pedagogical point of view.
Keywords: physical qualities; development